Dynamic lateral crushing of empty and sandwich tubes - Fan, Zhihua. (2013)
The dynamic lateral crushing behaviour of short empty and sandwich circular tubes is examined in this paper. Unlike the conventional impact method, the specimens were placed on the bottom platen of an Instron machine with a constant upwards velocity and then the tube collided with the fixed upper rigid platen. Load-deflection curves of empty tubes were first obtained and analysed. From the viewpoint of deformation modes and plastic strain energy absorbed by the tube quadrants around the proximal surface and distal surface, a critical velocity of impact is determined which corresponds to a mode change. A relationship is found to exist between the critical velocity and thickness-to-diameter ratio as well as the yield stress and density of the material. To understand the dynamic crushing behaviour of short aluminium foam-filled sandwich tubes by two rigid platens, further tests and corresponding finite element analysis were performed, respectively. Similar to the observations in the quasi-static tests, the mode of dynamic collapse is bending, with the formation of plastic bending zones accompanied with core crushing. Corresponding FE models for ABAQUS/Explicit were developed and validated against the experimental observations. Detailed deformation features and energy absorption characteristics during the crushing process were identified. It was found that increasing the compression velocity leads to an increase in the total internal plastic energy dissipation for both empty and sandwich tube. The propagation of plastic bending in the form of double-moving-hinges is the main mechanism of energy dissipation, as opposed to the low velocity impact which involves stationary plastic deformation zones.